Pengaruh Keputusan Investasi dan Kebijakan Dividen Terhadap Nilai Perusahaan LQ45 di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Annisya Fadilla; Mira Nurhikmat; Yulaikah (Indonesia Economic Journal, 2025)
This study aims to analyze the influence of investment decisions and dividend policy on firm value. Rapid economic development in Indonesia has increased business competition, pushing companies to maximize their value to attract investors and achieve optimal profits. Firm value, reflected in stock prices, is crucial for investors as it indicates shareholder prosperity. Investment decisions, proxied by the Price Earning Ratio (PER), and dividend policy, proxied by the Dividend Payout Ratio (DPR), are two key factors influencing firm value.The research employed a quantitative descriptive approach, analyzing secondary data from the annual reports of LQ45 companies on the IDX. The study sample consisted of 10 LQ45 companies selected using a purposive sampling method. Data analysis was conducted using multiple linear regression with SPSS 20, preceded by classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). The results indicate that investment decisions (PER) partially have a positive and significant effect on firm value (PBV) with a t-value of 2.324, meaning that thitung > ttabel (2.324 > 1.684) and a significance level of < 0.05 (0.025 < 0.05) H0 is rejected and Ha is accepted. Dividend policy (DPR) partially does not have a significant effect on firm value(PBV) with a t-value of -0.478, meaning that thitung > ttabel (-0.478 < 1,684) and a significance level of < 0.05 (0.638 > 0.05), indicating that H0 is accepted and Ha rejected. Simultaneously, investment decisions and dividend policy significantly influence firm value, with an Ftabel Value of 3.23, meaning that Fhitung > Ftabel (12.511> 3.23) and a significance level of p-value < 0.05 (0.000 < 0.05), trus H1 is a accepted.